2006
DOI: 10.1109/iembs.2006.4397768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Respiration in Heart Rate Variability (HRV) Analysis

Abstract: Beat-to-beat changes in cardiac signals or heart rate variability (HRV) is controlled by the two branches of Autonomic Nervous System (ANS) in a very complex manner. Although traditional HRV (tHRV) analysis has shown to provide information on cardiac ANS control, it often fails to isolate the effect of two branches in HRV signals. This problem becomes more obvious especially at low respiratory rates since parasympathetic activity shifts into lower frequencies and overlaps the frequency interval where sympathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…It has been shown the controlled breathing enables easier separation of the LF and HF bands. 6,27 However, controlled metronome breathing will also increase the HF band and thereby it may shift the sympathovagal balance toward vagal predominance. 28 It should be noted that the sample sizes are relatively small in the patient groups with late stage complications.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown the controlled breathing enables easier separation of the LF and HF bands. 6,27 However, controlled metronome breathing will also increase the HF band and thereby it may shift the sympathovagal balance toward vagal predominance. 28 It should be noted that the sample sizes are relatively small in the patient groups with late stage complications.…”
Section: Discussionmentioning
confidence: 99%
“…1, the intervals of breathing become larger and the quantity of one breath increases as a person becomes stabilized physically and mentally when the human body enters deep sleep. In reality, it can be activated in a much lower range than this one (Aysin and Aysin, 2006;Choi et al, 1999;Cammann and Michel, 2002). Therefore, in this study, it was evaluated by expanding the HF range into 0.1 ~ 0.4 Hz.…”
Section: Edr Evaluationmentioning
confidence: 99%
“…So, in this study, the level of activation is evaluated through the PSD of 0.1 ~ 0.4 Hz section. If we compare the HF range section among the HF range of the HRV and the frequency range of the EDR extracted from the ECG, we can evaluate how a well measured ECG reflects breathing signals (Aysin and Aysin, 2006;Choi et al, 1999;Cammann and Michel, 2002). …”
Section: Autonomic Nervous System and Heart Rate Variabilitymentioning
confidence: 99%
“…The LF range from 0.04 Hz to 0.15 Hz is typically considered the marker of sympathetic activity, whereas the HF range from 0.15 Hz to 0.4 Hz is referred to as the marker of parasympathetic activity. [12][13][14] Recent studies have suggested that the HF component of HRV is affected by respiration. 12,15 At lower respiration rates, the HF component that reflects parasympathetic activity shifts toward the lower frequency range and overlaps with the range of the LF component that is defined for sympathetic activity.…”
mentioning
confidence: 99%
“…[12][13][14] Recent studies have suggested that the HF component of HRV is affected by respiration. 12,15 At lower respiration rates, the HF component that reflects parasympathetic activity shifts toward the lower frequency range and overlaps with the range of the LF component that is defined for sympathetic activity. Consequently, traditional methods for HRV analysis (tHRV) that are based on fixed LF and HF ranges frequently result in over-estimations at low respiratory rates.…”
mentioning
confidence: 99%